The Impact of Digitalization of Social Services on the Economic Efficiency of Public Expenditure - CHERBA, Vita; KORIAHINА, Tetiana; RIABOSHAPKA, Olena; PETROSYAN, Arsen; SKRYLNIK, Andrey (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025, 2025)
The digitalization of public administration is a key direction for improving the efficiency of budgetary resource use, especially in the field of social welfare. The implementation of digital technologies in social services contributes to the reduction of bureaucratic costs, acceleration of decision-making processes, and increased transparency of funding. The purpose of this study is to assess the impact of digitalization of social services on the economic efficiency of public spending. Methods of comparative analysis, regression modeling, and correlation assessment were used based on data from 15 countries in Europe, North America, and Asia. The study revealed a significant positive correlation between the level of digitalization and the reduction of administrative costs. In countries with a high level of digital services, adminis-trative costs for social programs decrease to 2 - 3% of total social expenditures, while in countries with a low level of digitalization, these costs can exceed 8 - 10%. Moreover, the introduction of digital platforms, such as “Diia” in Ukraine, helps reduce the time required for processing social assistance applications by 40 - 50%, which aligns with trends in other digitally advanced countries. The results of the study have significant practical value for optimizing social spending and developing policies for the digital transformation of public services. Recommendations are proposed to address digital inequality, enhance cybersecurity, and expand digital literacy programs to ensure equal access to electronic social services. Future research prospects include analyzing the long-term economic effects of digitalizing social welfare and evaluating its impact on the social inclusion of various population groups.